TRADITIONAL THERAPEUTIC FOOD OF PLANT AND ANIMAL ORIGIN AMONG PEOPLES OF THE NORTH CAUCASUS AND DAGESTAN (XIX–XX сс.) - Alieva, Patimat Sapiulaevna; Bogatyreva, Svetlana Nikolaevna (History, Archeology and Ethnography of the Caucasus, 2022)
The culture and traditions of peoples associated with nutrition, like all other traditions adopted by a certain ethnic group, represent a separate independent and original category. Nevertheless, only due to a comprehensive analysis of spiritual and material culture that we can identify the commonality and distinctive features of the traditional elements of various ethnic groups. This article presents and describes the historical variations of use of medicinal food of plant and animal origin among the peoples of the North Caucasus. We have carried out a comparative analysis of the composition, technologies of cooking and use of traditional medicinal food among various ethnic groups, as well as an analysis and structuring of literature sources on this subject. The study of the traditional food of peoples combines a huge layer of ethnographic oral and written evidence, archaeological sources, medical, physiological, biochemical, psychological studies, folklore, hundreds of various rites and rituals, prohibitions and calendar regulations, religious beliefs. The relevance of the conducted research lies in addressing the sources of numerous possibilities of applying the centuries-old and diverse experience of the peoples of Russia in the field of health-improving use of plant and animal-based products. Numerous scientific conferences devoted to the problems of application, effects on the body, synergy of the chemical composition of medicinal and animal products indicate an increasing interest in the healing power of nature. In addition, it highlights the issues of the unique beneficial properties of phytopreparations, organopreparations and animal-based preparations. As a result of the conducted research, it is possible to conclude about the geographical variability of the composition of products of plant and animal origin depending on the territory of residence of a certain ethnicity. The formation of traditional features has a specific orientation in the field of economic activity and largely depends on the natural conditions of residence.